Economic Analysis of Locust Beans Processing and Marketing in Ilorin, Kwara State, Nigeria - Farayola, CO; Okpodu, V; Oni, OO (International Journal of Agricultural Research, Innovation and Technology, 2013)
This study was designed to estimate the economic analysis of locust bean processing and marketing in Ilorin, Kwara State, Nigeria. Primary data was used and purposive sampling technique was adopted to select the respondents used for the study. A total number of 60 respondents were interviewed. The data collected were analyzed using inferential statistical tool such as regression analysis. Budgetary analysis technique was also used to analyze the profitability of locust bean processing and marketing in the study area. Majority of the processors and marketers are making profits; 68.3% operate above breakeven point while 26.7% operate at breakeven point and the rest 5% was below the breakeven point, this indicates that they neither profit nor lost. The regression analysis result shows that quantity processed, family size and years of experience in processing are significant at 1%, 5% and 10% respectively while education level and stall rent is negative and significant at 1% and 5% respectively. F- Test also explained that independent variables are jointly significant at 1% probability level with an adjusted R2 of 78.9%. The overall rate of return on investment indicates that average rate of return is 0.5 (50%), which is positive. It is therefore concluded that profit made by the processors and marketers can be improved on by increasing the quantity of locust bean being processed through adoption of newly discovered method of processing and improved method of preservation, packaging and marketing of the product to international standard by reducing the odour of the product without the loss of essential nutrients and palability in order to generate foreign exchange. Also, rules and regulations against cutting of economic trees for alternative uses should be enforced to maximize their values. DOI: http://dx.doi.org/10.3329/ijarit.v2i2.14012 Int. J. Agril. Res. Innov. & Tech. 2 (2): 36-43, December, 2012